Identification of new sources and mapping of QTL for FHB resistance in Asian wheat Germplasm - Yu, Jianbin (Kansas State University, 2007)
Growing resistant cultivars is an economically effective method to control wheat disease Fusarium head blight (FHB) caused by Fusarium graminearum. Ninety-five wheat lines mainly from China and Japan were evaluated for resistance to initial infection (type I), spread of symptoms within a spike (type II), and deoxynivalenol (DON) accumulation in infected grains (type III). Most of lines were resistant or moderately resistant, 15 lines had DON content lower than 2 ppm and six lines showed a high level of resistance for all the three types. Deoxynivalenol content was significantly correlated with type II, but not type I resistance. Fifty-nine of the ninety-five lines were evaluated for genetic diversity on the basis of amplified fragment length polymorphism (AFLP) and simple sequence repeats (SSRs). Genetic relationships among these lines were consistent with pedigrees and their geographic distribution. Chinese lines had broader genetic diversity than Japanese lines. Sumai 3 is a widely used Chinese variety for FHB-resistant breeding in the US and elsewhere. Haplotype patterns of the SSR markers linked to FHB resistance quantitative trait loci (QTL) on chromosomes 3BS, 5AS and 6BS of Sumai 3 indicated that only a few Sumai 3 derivatives carry all of these Sumai 3 QTL. SSR data also suggested that these QTL in Sumai 3 were derived from Chinese landrace Taiwan Xiaomai. Some highly resistant lines may carry novel QTL for FHB-resistance QTL, and need further investigation. A mapping population of 139 recombinant inbred lines derived from the cross of Wangshuibai (resistant Chinese landrace)/Wheaton (susceptible cultivar) was genotyped with more than 1300 SSR and AFLP markers. Five QTL for type I resistance were detected on chromosome arms 3BS, 4BS, 5DL, 3AS, and 5AS; seven QTL for type II resistance on 3BS, 1AL, 5AS, 5DL, 7AL, and 3DL; and seven QTL for type III resistance on 3BS, 5AS, 1AS, 5DL, 1BL, and 7AL. These QTL together explained 31.7%, 64%, and 52.8% of the phenotypic variation for FHB type I, II, and III resistance, respectively. QTL on 5AS, the distal end of 3BS, and 5DL contributed to all three types of resistance. FHB resistance QTL identified in Wangshuibai can be used in developing wheat cultivars with enhanced FHB resistance by pyramiding FHB resistance QTL from other sources.
Keywords: Fusarium head blight (FHB); Quantitative trait locus (QTL); Agriculture, Agronomy (0285)